Enhanced Quality of Service (QOS) for MANET Routing Protocol Using a Distance Routing Effect Algorithm for Mobility (DREAM) - Hmeed, Assef Raad; A. Hammad, Jamal; J. Obaid, Ahmed (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In mobile ad hoc networks (MANETs), cell hubs can not only be a piece of the system but also leave or change their position inside it, so the network’s topology can change unexpectedly and in unusual ways. A MANET is a self-arranging, versatile framework. Ad hoc on-demand distance vector routing (AODV) does not help quality of service (QoS) and has no heap adjusting component. The QoS steering highlight is simple in a constant, independent multi-jump cell network for real-time applications and, furthermore, in a cell network to interconnect systems with QoS help. In this research, we improve the QoS directing of AODV convention by utilizing the area-based abilities of the Distance Effect Routing Algorithm for Mobility (DREAM). In this DREAM convention, the exact records of every hub are kept in the network, considering different hubs which may be taking part in the steering system. The portable basis of the network is anticipated with the guidance of the DREAM convention, so the flooding of foundation bundles is best brought to that zone by ensuring that the overhead for discovering excursion spots is limited. The DREAM convention improves the QoS of the AODV steering convention. In this investigation, we're thinking about the excellent situation of a cell-hubs approach, at least as far as an assortment of hubs in the network. In addition, the demonstration of the proposed QoS steering is better with the limited overhead.